Fluid dynamics analyses of the intrahepatic portal vein tributaries using 7-T MRI. Issue 11 (November 2021) - Oshima, Yu; Ogiso, Satoshi; Imai, Hirohiko; Nakamura, Masanori; Wakama, Satoshi; Tomofuji, Katsuhiro; Ito, Takashi; Fukumitsu, Ken; Ishii, Takamichi; Matsuda, Tetsuya; Taura, Kojiro
Abstract: Background: Assessing portal vein (PV) hemodynamics is an essential part of liver disease management/liver surgery, yet the optimal methods of assessing intrahepatic PV flow have not yet been established. This study investigated the usefulness of 7-Tesla MRI with hemodynamic analysis for detecting small flow changes within narrow intrahepatic PV branches. Methods: Flow data in the main PV was obtained by two methods, two-dimensional cine phase contrast-MRI (2D cine PC-MRI) and three-dimensional non-cine phase contrast-MRI (3D PC-MRI). Hemodynamic parameters, such as flow volume rate, flow velocity, and wall shear stress in intrahepatic PV branches were calculated before and after a meal challenge using 3D PC-MRI and hemodynamic analysis. Results: The hemodynamic parameters obtained using 3D PC-MRI and 2D cine PC-MRI were similar. All intrahepatic PV branches were clearly depicted in eight planes, and significant changes in flow volume rate were seen in three planes. Average and maximum velocities, cross-sectional area, and wall shear stress were similar between before and after a meal challenge in all planes. Conclusion: 7-Tesla 3D PC-MRI combined with hemodynamic analysis is a promising tool for assessing intrahepatic PV flow and enables future studies in small animals to investigate PV hemodynamics associated with liver disease/postoperative liver recovery. Graphical abstract: Image 1